Osmotic stress on genetically transformed tobacco plant seeds - Trombin-Souza,Michele (2017)
Abstract: Salinity and water deficit limit the productivity of several crops; thus, studies related to the genetic transformation of seeds in a model plant, such as tobacco, can be an alternative to minimize negative impacts caused by environmental conditions. The purpose of this work was to evaluate the tolerance to osmotic stress of seeds from genetically transformed tobacco plants, with the introduction of the proline-synthesizer gene (p5csf129a), under salinity and water deficit conditions. To do so, five events with differences in proline content were selected, ranging from 0.70 to 10.47 µmoles.g-1 of fresh mass. The used saline concentrations were: zero (distilled water); 50; 100; 150 and 200 mmol.L-1 of NaCl, whereas for the water deficit, simulated with PEG 6000, the following osmotic potentials were used: zero (distilled water); -0.2; -0.4; -0.6 and -0.8 MPa. Each tested treatment was evaluated through germination, first germination count and germination speed index tests. It is possible to conclude that seeds from genetically transformed tobacco plants with overexpression of the gene p5csf129a, a proline synthesizer, are more tolerant to osmotic stresses. Tabacco seeds with a proline content of 10.47 µmol.g-1 showed a better perfomance, revealing higher physiological potential.